1995
DOI: 10.1093/jnci/87.6.437
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Immunoglobulin G Antibodies Against Human Papillomavirus Type 16 Capsids With Anal Epidermoid Carcinoma

Abstract: Exposure to HPV16 or related viruses appears to be a major risk factor in the majority of anal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 0 publications
1
36
1
1
Order By: Relevance
“…By applying HPV serology, a marker of both past and present HPV infection, it has been possible to investigate possible temporal associations of HPV infection with anal cancer. Previously, a serologic association of HPV 16 with incident anal cancer has been reported (Heino et al, 1995). In our previous, prospective study, no association of HPV and anal cancer was found, although a high, but insignificant risk was found for perianal skin cancer (Bjørge et al, 1997a).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…By applying HPV serology, a marker of both past and present HPV infection, it has been possible to investigate possible temporal associations of HPV infection with anal cancer. Previously, a serologic association of HPV 16 with incident anal cancer has been reported (Heino et al, 1995). In our previous, prospective study, no association of HPV and anal cancer was found, although a high, but insignificant risk was found for perianal skin cancer (Bjørge et al, 1997a).…”
Section: Discussionmentioning
confidence: 69%
“…A serologic association of HPV 16 with incident anal cancer has been shown (Heino et al, 1995). In a study of the role of HPV in non-cervical anogenital cancers, we found that HPV 16 seropositivity conferred an increased risk for noncervical anogenital cancers, but not for anal cancer (Bjørge et al, 1997a).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…The majority of the assays undertaken by participants were direct EIAs, involving coating EIA plates with VLPs whereas others used capture assays. 2,[11][12][13][14][15][16][17] One participant used an RIA 1 and the remaining laboratories EIAs. One participant used bacterially expressed and affinity-purified L1 capsid proteins fused to glutathione S-transferase as antigens.…”
Section: Assay Methodsmentioning
confidence: 99%
“…Eligible women first donated a 10 ml serum sample that was screened for presence of HPV antibodies by a standard ELISA in 1 laboratory, as described previously. 11 A negative control serum sample was collected from an adult woman who had reported no sexual experience and a positive control serum sample from a woman with >4 lifetime sexual partners who had been seropositive for antibody to capsids of HPV 6,11,16 and 18 in the initial screening. In all, 16 women were selected and donated blood for inclusion in the study.…”
Section: Study Samplesmentioning
confidence: 99%